Identifying priority value chains in Tanzania - Thurlow, James; Randriamamonjy, Josee; Benson, Todd (Michigan State University, 2018)
Value chain development is increasingly perceived as an important approach for agricultural development in developing countries. This paper uses a Rural Investment and Policy Analysis (RIAPA) model for the mainland Tanzania economy to identify the agricultural activities and value-chains whose expansion will be most effective at fostering economic development along four dimensions: generating economic growth in the agricultural-food sector of Tanzania; reducing national and rural poverty; generating employment; and improving nutrition by diversifying diets. The results of scenarios run through the model suggests that there is no single value-chain that can achieve all of the policy objectives. Instead, a more balanced portfolio of value-chains would not only enhance agriculture’s future contribution to poverty reduction and economic growth, but also promote faster rural transformation and dietary diversification, both of which are needed to create job opportunities and improve nutrition outcomes over the longer-term. The analysis suggests that vegetables, coffee, milk, cotton, nuts, and oilseeds should be considered as “priority” value-chains, because these are the most effective at achieving multiple policy objectives. Other value-chains that meet several of the development objectives considered include maize, fishing, wheat and barley, rice, cattle, and poultry and eggs.